1996
DOI: 10.1177/089686089601600114
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Leached Di(2-Ethylhexyl)Phthalate in Patients Undergoing Capd Treatment

Abstract: Objectives To evaluate the degree of exposure to and the fate of di(2-ethylhexyl)phthalate (DE HP) and its major derivatives mono(2-ethylhexyl)phthalate (ME HP), 2-ethylhexanol (2-EH), and phthalic acid (PA) in patients undergoing regular continuous ambulatory peritoneal dialysis (CAPD) during a 4-hour dwell period. Design Prospective, controlled. Setting Teaching hospital, Department of Nephrology. Participants Seven elderly patients on stable CAPD using Fresenius instruments and dialysate and 6 agematched he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 13 publications
4
11
0
1
Order By: Relevance
“…The impact of MP on humans is not yet fully understood, however, many chemicals that are used in plastic production and are known to be toxic, for example, bisphenol A (BPA), polybrominated diphenyl ethers (PBDE), and tetrabromobisphenol (TBBPA) have already been detected in human tissues and biological fluids . It has also been reported that additives, for example, di(2‐ethylhexyl)phthalate (DEHP), can leach from medical supplies made of PVC and accumulate in the blood of haemodialysis patients . Moreover, the presence of MP in seafood, for example, bivalves cultured for human consumption, has already been shown .…”
Section: Uptake and Effects Of Mp In Living Organismsmentioning
confidence: 99%
“…The impact of MP on humans is not yet fully understood, however, many chemicals that are used in plastic production and are known to be toxic, for example, bisphenol A (BPA), polybrominated diphenyl ethers (PBDE), and tetrabromobisphenol (TBBPA) have already been detected in human tissues and biological fluids . It has also been reported that additives, for example, di(2‐ethylhexyl)phthalate (DEHP), can leach from medical supplies made of PVC and accumulate in the blood of haemodialysis patients . Moreover, the presence of MP in seafood, for example, bivalves cultured for human consumption, has already been shown .…”
Section: Uptake and Effects Of Mp In Living Organismsmentioning
confidence: 99%
“…High concentrations of DEHP have been measured in blood of patients undergoing dialysis, caused by migration of the plasticizer from plastic medical devices (Pollack et al. , 1985; Mettang et al. , 1996).…”
Section: Phthalatesmentioning
confidence: 99%
“…Von vielen Chemikalien, die in der Kunststoffproduktion eingesetzt werden, ist jedoch bekannt, dass sie toxisch sind, wie Bisphenol A (BPA), polybromierte Diphenylether (PBDE) und Tetrabrombisphenol A (TBBPA), die bereits in menschlichem Gewebe und Körperflüssigkeiten nachgewiesen wurden . Es wurde weiterhin berichtet, dass Additive wie Di(2‐ethylhexyl)phthalat (DEHP) aus medizinischem Zubehör, das aus PVC besteht, austreten kann und sich im Blut von Hämodialyse‐Patienten anreichert . Weiterhin wurde gezeigt, dass MP in Meeresfrüchten, z.…”
Section: Aufnahme Von Mp Und Daraus Resultierende Effekte Auf Lebendunclassified